The effectiveness and safety of acupuncture for scoliosis: A protocol for systematic review and/or meta-analysis. Issue 50 (11th December 2020) - Choi, Seong-Kyeong; Jo, Hyo-Rim; Park, Seo-Hyun; Sung, Won-Suk; Keum, Dong-Ho; Kim, Eun-Jung
Abstract: Background: Scoliosis is a disease that affects all age groups and alters the three-dimensional deviation of the spinal axis. It is diagnosed when Cobb angle presents over 10 degrees and the reasons include aging, traumatic injuries, unknown origin, and disorders of congenital, neurological, musculoskeletal, and connective tissue. Scoliosis treatments are divided into surgical and conservative options. Surgery can correct the curved spine but has associated risks and economic burden. Conservative treatments, particularly bracing, prevent the progression of scoliosis, but still remains potential ingredient of curvation and patients poor compliance. Recent studies reported that various types of acupuncture can improve the curvation and the associated pain. However, there has been no systematic review on this issue. Therefore, this study will review the effectiveness and safety of acupuncture on scoliosis. Methods: Searching randomized controlled trials about the use of acupuncture for scoliosis will be performed using multiple electronic databases, manual search, and contact to authors e-mail if needed. We will select studies by the pre-defined criteria and summarize the data on study participants, interventions, control groups, outcome measurement, adverse events, and risk of bias. The primary outcome will be the Cobb angle, which is objective, and the secondary outcomes are associated with patient-centered indices (pain, functional status, and quality of life), which are subjective and adverse events. We will use Review Manager software (Version 5.3; Copenhagen; The Nordic Cochrane Center, The Cochrane Collaboration, 2014) to perform a meta-analysis and Cochrane Collaboration "risk of bias" tools to assess the risk of bias. Results: Our study will investigate the clinical evidence on the effectiveness and safety of acupuncture on scoliosis. Conclusion: Our study will be informative to scoliosis patients, clinicians, policy makers, and researchers working with conservative management for scoliosis.